Prototype Alat Penyiram Tanaman Otomatis dengan Sensor Kelembaban dan Suhu Berbasis Arduino - Shamaratul Fuadi; Oriza Candra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Quality plants are produced by observing soil moisture and plant temperature. Plants humidity and temperature are affected by plant irrigations system. Therefore, this Final Project aims to make a plant sprinklers that can control water discharge according to plant needs. Using the Soilmoisture Sensor which functions as a reader of plant soil moisture and DHT11 as a reader of the air temperature around the plant. Then the relay module functions to activate and deactivate the water pump. LCD is used to display the data results and the ESP8266 Module is also used as a display of the results of sensor data, which will be sent to the thingspeak.com website